Arrhythmogenic mitral valve prolapse—a systematic review of ventricular arrhythmia and sudden cardiac death outcomes before and after mitral valve surgery - James N. Cameron; Nigel Sutherland; Chee Loong Chow; Hui‐Chen Han; Matias Yudi; Rajiv Mahajan; Anand Ganesan; Avi Sabbag; Kristina H. Haugaa; Jai Raman; Prashanthan Sanders; Omar Farouque; et al. (Journal of Arrhythmia)
Abstract Background Several autopsy and observational studies have investigated the link between mitral valve prolapse (MVP) and sudden cardiac death (SCD) given the well accepted yet rare occurrence of ventricular arrhythmias (VA). Whether surgical intervention for arrhythmogenic MVP (aMVP) reduces VA and SCD risk remains unknown. Methods A systematic literature review was conducted using the PubMed database in December 2024. Studies documented in English were included if patients had undergone mitral valve (MV) surgery (MVS; repair or replacement) for MVP with documented rates of VA or SCD pre‐ and postintervention. Results Sixteen identified studies (8 cohort and 8 case studies) comprised 1233 patients (receiving medical or surgical treatment) with a pooled mean age of 61.5 years and 41.9% being female. A total of 657 MVP patients underwent MVS. Seven cohort studies reported rates of VA pre‐ and postintervention, with six of these and all case studies reporting a significant reduction. The remaining cohort study reported a reduction in SCD. Conclusions This systematic review indicates a reduction in VA following current guideline‐directed MVS for MVP. However, a residual risk of VA and SCD may remain postintervention.